Food taboo practices and associated factors among pregnant women in Sub-Sahara Africa: a systematic review and meta-analysis - Aysheshim Kassahun Belew; Berhanu Mengistu; Ayenew Molla Lakew; Esmeal Ali Muhammad (Journal of Health, Population and Nutrition)
Abstract Background Even though maternal nutrition has improved, food taboos and poor dietary practices during pregnancy can still lead to nutrient deficiencies, increasing the risk of complications for both mothers and children. Therefore, this study aimed to generate pooled evidence from across different countries in Sub-Saharan Africa to inform effective prevention actions. This meta-analysis aims to determine the pooled prevalence of food taboo practices and identify associated factors among pregnant women in Sub-Saharan Africa. Methods This study systematically reviewed relevant articles and reports from databases including Embase, MEDLINE, Science Direct, PubMed, Google, and Google Scholar. The Newcastle–Ottawa Scale assessed article quality. Data extraction and analysis were done using Excel and STATA 17, respectively. Heterogeneity was assessed using Cochran's Q test and the I2 statistic, with a random effects model employed for meta-analysis. Publication bias was evaluated and addressed using Duval and Tweedie's Trim and Fill analysis. Results A total of fifty-eight studies with 20,262 pregnant women were included in this meta-analysis. The pooled proportion of food taboo practices reported by the 58 studies was 41% (95% CI: 34, 48%). In the subgroup analysis, the pooled proportion of food taboo practices for studies conducted in urban areas was 40% (95% CI: 32, 48%), while it was 43% (95% CI: 32, 56%) among rural residents. Factors associated with food taboo practices among pregnant women included being unable to read and write (AOR = 2.64%; 95% CI: 1.79–3.90; I2 = 56.9%), not receiving antenatal care follow-up (AOR = 3.73%; 95% CI: 2.83–3.90; I2 = 55.1%), and poor maternal nutrition knowledge (AOR = 3.33%; 95% CI: 1.56–7.09; I2 = 84.3%). Conclusion According to this review, over two out of every five pregnant mothers practiced food taboos in the region. The educational status of the mother, antenatal care follow-up, and maternal nutrition knowledge were factors affecting food taboo practices among pregnant women. Therefore, emphasis should be given to the uptake of antenatal care follow-up to improve maternal nutrition knowledge and nutritional status.